ROLE OF MOTIVATION TO INNOVATION BEHAVIOR WITH KNOWLEDGE AS MEDIATING VARIABLE IN FEMALE BUSINESS OWNERS - Helmi Buyung Aulia Safrizal; Vasio Sarmento Soares; Muhammad Ali Ahmad (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
The objective of this research is to examine and analyze predictors of innovation behavior, namely motivation (extrinsic and intrinsic) and good knowledge. Therefore, it employs a quantitative research methodology, using a survey to collect data. Two hundred fifteen female respondents in SMEs in Madura have been collected for the data processes using SEM-PLS. The results indicate that all hypotheses were accepted. Both direct and indirect hypotheses demonstrate that knowledge can serve as a mediating variable in the indirect influence test. This research shows that good knowledge has a positive and significant impact. Similarly, the direct influence test also shows positive and significant results. The independent variable on adequate knowledge can be a good predictor of success as innovative behavior in making art, specifically producing batik. It has been one of cultural characteristics of the Maduranese community. The novelty in this research lies in the success of the valuable knowledge possessed by women in creating more valuable products.